The Influence of Human Resource Management Strategy and Job Satisfaction on Volunteer Retention - Permana, Hilman; Pratiwi, Luthfi Sekar; Damanik, Rinda Putri Agusti; Purnamasari, Pupung (Peneliti.net, 2025)
This research aims to explore the impact of human resource strategies on volunteer retention in international humanitarian organizations, with a focus on job satisfaction as a mediating variable. Quantitative methods were used, with data analysis using the Partial Least Square (PLS) technique. Data was collected through a questionnaire with a Likert scale (1-5) and in-depth interviews, involving 200 volunteer respondents from organizations such as UNHCR, ICRC, and MSF. Research findings show that human resource strategies that include training, career development, and providing incentives have a significant impact on volunteer retention. In addition, job satisfaction acts as a significant mediator in this relationship. Aspects such as recognition, interpersonal relationships, and working conditions play an important role in strengthening loyalty and extending the duration of volunteers' contributions. The results of this research highlight the importance of implementing a comprehensive human resource strategy to maintain the involvement of volunteers, especially from the younger generation